Hydro-institutional mapping in the Steelpoort River Basin, South Africa - Stimie, C.; Richters, E.; Thompson, H.; Perret, S.; Matete, M.; Abdallah, K.; Kau, J.; Mulibana, E. (International Water Management Institute, 2001)
Volume 1 of the study on Hydro-Institutional Mapping of the Olifants River Basin. This study aims to give an overview of water users and influences on water use by institutions in the Steelpoort river basin, a sub-basin of the Olifants. Describes a general methodology and framework for setting out the HIM for a river basin and presents findings from case studies in the basin. The hydro-institutional interactions among all types of water users in a South African river basin are also described.